Pharmacy services at the Tokyo 2020 Olympic and Paralympic Games: perspectives of the pharmacy workforce. (5th October 2022) - Kasashi, Kumiko; Sato, Ayaka; Stuart, Mark; Thomas, Trudy; Kim, Sung Hwa; Jang, Da Mi; File, Hayley; Suzuki, Satomi; Rhie, Sandy Jeong
Abstract : Objectives: To evaluate the awareness of the volunteer pharmacy workforce of medication use and their satisfaction with the pharmacy services of the Tokyo 2020 Olympic and Paralympic Games from a pharmacist's perspective. Methods: A questionnaire was developed from related articles in published peer-reviewed journals and modified prior to distribution to the whole population of pharmacists serving at the Tokyo 2020 Olympic and Paralympic Games. Validity tests were conducted based on expert opinions and Cronbach's alpha (0.79). The questionnaire consisted of demographics (11 questions), knowledge of medication use in sports (8 questions) and satisfaction on the provision of the service (5 questions). Responses using a 5-point-Likert scale, from strongly agree (5) to strongly disagree (1), and two free text questions were analysed with descriptive statistics. Results: The response rate was 86% (n=32/37). Overall, the pharmacists reported a high awareness of medication use. Specifically, questions on the prohibited list of medications (mean 4.0±SD 0.7), COVID-19 policy (3.8±0.9), use of alternative non-prohibited medications (3.6±1.0) and therapeutic use exemptions (3.5±0.9). Moreover, they rated high satisfaction with the pharmacy service they provided. However, rates were ≤3 for knowledge of the International Olympic Committee Needle Policy (2.6±1.0), Medication Importation Declaration (2.9±1.0) and communication skills (3.0±1.0). Conclusion: Pharmacists were confident and satisfied with the pharmacy service at the games. The study confirms the importance of prior training and education. Game-specific policies and strategies to improve communication skills should be included in the pharmacy education for future Games.